2017
DOI: 10.7759/cureus.1832
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Peripheral Nerve Field Stimulation for Intractable Coccygeal Pain: A Case Study Using Dual Lead Intercommunication

Abstract: Coccygeal pain is a difficult chronic pain problem with mixed response to various treatments. This is a report of a case of coccygeal pain that after failing various conservative and interventional procedures over five years was evaluated with a temporary peripheral sacral fascial lead followed by implantation of bilateral sacral paramedian leads for peripheral nerve field stimulation (PNFS). This resulted in marked pain control and resumption of full activity. The visual analog scale (VAS) pain score improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…These results would suggest that the majority of providers are either targeting single nerves or only targeting two nerves simultaneously for less than half of their cases. One case study found marked pain control from bilateral peripheral nerve field stimulation (PNfS) in intractable coccygeal pain 25 but the PNS data for a comparison between efficacy of dual‐lead implants and single‐lead implant is limited. Further, additional studies are needed to distinguish between physician perception of clinical efficacy from dual‐lead implants that target unilateral versus bilateral limbs.…”
Section: Discussionmentioning
confidence: 99%
“…These results would suggest that the majority of providers are either targeting single nerves or only targeting two nerves simultaneously for less than half of their cases. One case study found marked pain control from bilateral peripheral nerve field stimulation (PNfS) in intractable coccygeal pain 25 but the PNS data for a comparison between efficacy of dual‐lead implants and single‐lead implant is limited. Further, additional studies are needed to distinguish between physician perception of clinical efficacy from dual‐lead implants that target unilateral versus bilateral limbs.…”
Section: Discussionmentioning
confidence: 99%
“…D’Ammando et al28 employed PNFS on 22 patients with chronic refractory neuropathic pain and found that the clinical effect of PNFS was better on craniofacial postherpetic neuropathy (PHN) than on upper limb PHN; and of failed back surgery syndrome (FBSS) patients, pain in lumbosacral area achieved better analgesic effects than in perineal area. Granville et al29 used temporary bilateral sacral PNFS in the treatment of intractable coccyx pain and achieved good results.…”
Section: Discussionmentioning
confidence: 99%
“…PNS has been shown to be efficacious in several chronic pain conditions including trigeminal neuropathic pain [ 12 – 16 ], episodic cluster headache (supraorbital nerve stimulation) [ 17 , 18 ], chronic migraine/headache disorders (occipital nerve stimulation) [ 19 , 20 ], fibromyalgia (C2 area stimulation) [ 21 , 22 ], postherpetic neuralgia [ 23 26 ], complex regional pain syndrome type I [ 4 , 27 ] and type II [ 28 ], isolated peripheral neuropathy [ 29 ], ilioinguinal, iliohypogastric, and lateral femoral cutaneous neuralgia [ 30 ], back pain [ 31 ], foot pain (tibial nerve stimulation) [ 32 ], and coccydynia [ 21 , 33 ].…”
Section: Indications and Patient Selectionmentioning
confidence: 99%